SINR performance analysis of DFT spread generalized multi-carrier system - RUI Yun1; LI Ming-qi1; ZHOU Qin-ying1; ZHANG Xiao-dong1; YI Hui-yue1; HU Hong-lin1 (Tongxin xuebao)
A signal-to-interference-plus-noise ratio（SINR） performance analysis method of discrete fourier transform spread generalized multi-carrier（DFT-S-GMC） system was proposed.The closed-form SINR expression based on simpli-fied frequency-domain equivalent implementation structure and MMSE equalization for receiver is derived by channel frequency response and noise variance,considering inter-block（IFBT symbol） residual interference multiplexed in time domain.Moreover,it can be easily extended to multi-receive antenna.By simulation results,it is shown that with pro-posed equivalent SINR,the BLock error rate（BLER） performance of DFT-S-GMC over slow fading channel is well matched with that over AWGN channel.